Effect of freezing rates on the cell structure and physical characteristics of pineapple (Ananas Comosus Linn.Merr.) - Isidro, Dolores O.
Pineapple cubes were frozen at three different freezing rates, represented by the three freezing methods namely freezing by still air at -15°C, direct immersion in dry ice-ethanol bath at -38°C and by direct immersion in liquid nitrogen at -196°C. Results from both histological and physical tests showed that ultrafast freezing with liquid nitrogen preserved the textural properties of the plant tissues much better than rapid freezing or by slow freezing.